2013
DOI: 10.1016/j.ecss.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mobile demersal megafauna at artificial structures in the German Bight – Likely effects of offshore wind farm development

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Within the next few decades, large underwater structures of thousands of wind turbines in the northern European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 45 publications
(73 reference statements)
1
26
0
Order By: Relevance
“…Structurally complex habitats provide refuge against predation for decapods in their final larval stage (megalopae) and early juveniles. Artificial hard substrate such as wind turbines, shipwrecks and oil platforms are known to provide habitat and attract recruitment of crustaceans (Coolen et al, 2018, Krone et al, 2013, Page et al, 1999. The finding of high amounts of small individuals (CW: 10-60 mm) at wind turbines indicated that the upper construction parts of the WTF may also act as a nursery ground, and thus as an artificial larvae collector for C. pagurus (Krone et al, 2017, Krone et al, 2013.…”
Section: Early Settlementmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally complex habitats provide refuge against predation for decapods in their final larval stage (megalopae) and early juveniles. Artificial hard substrate such as wind turbines, shipwrecks and oil platforms are known to provide habitat and attract recruitment of crustaceans (Coolen et al, 2018, Krone et al, 2013, Page et al, 1999. The finding of high amounts of small individuals (CW: 10-60 mm) at wind turbines indicated that the upper construction parts of the WTF may also act as a nursery ground, and thus as an artificial larvae collector for C. pagurus (Krone et al, 2017, Krone et al, 2013.…”
Section: Early Settlementmentioning
confidence: 99%
“…Artificial hard substrate such as wind turbines, shipwrecks and oil platforms are known to provide habitat and attract recruitment of crustaceans (Coolen et al, 2018, Krone et al, 2013, Page et al, 1999. The finding of high amounts of small individuals (CW: 10-60 mm) at wind turbines indicated that the upper construction parts of the WTF may also act as a nursery ground, and thus as an artificial larvae collector for C. pagurus (Krone et al, 2017, Krone et al, 2013. Besides structural complexity megalopae in general actively select a habitat suitable for settlement by detecting abiotic and biotic environmental stimuli such as changes in temperature and salinity, and chemical cues derived from conspecific adults and/or nursery areas (Forward et al, 2001).…”
Section: Early Settlementmentioning
confidence: 99%
“…Belgian OWP monitoring programme, Reubens et al, 2014a, b) or jacket foundations (e.g. German OWP monitoring programme, Krone et al, 2013a). Preliminary comparisons already demonstrated a difference in ecology between the different foundation types (Krone, 2014).…”
Section: Basic Monitoringmentioning
confidence: 99%
“…cod and pouting (Reubens et al, 2014b), but several invertebrate (e.g. edible crab Cancer pagurus and European lobster Homarus gammarus) and fish species common to OWPs, were so far less investigated (Krone, 2012;Krone et al, 2013a). Investigations of their habitat use for example would shed light on the key habitat features that are essential to maintain a sustained local population of these species.…”
Section: Targeted Monitoringmentioning
confidence: 99%
“…On the other hand, artificial reef effects can result in negative ecological impacts since their associated community composition may not be the same as natural reef communities in the same geographical area, which could lead to ecosystem changes as noted in research on the foundations of the Alphaventus offshore windfarm [67,68]. Artificial reef effects may vary depending on the existing ecosystem, geographical location and specific environmental features [69].…”
Section: Artificial Reef Effectsmentioning
confidence: 99%